Impact Force Magnitude Analysis of an Impact Pendulum Suspended in a Vibrating Structure - R.R. Aguiar; H.I. Weber (Shock and Vibration)
The purpose of this work is the experimental investigation and the mathematical modeling of the impact force behavior in a vibro-impact system, where an impact pendulum is mounted on a cart that moves with a prescribed displacement. The dynamics of the system will be evaluated considering different excitation frequencies and changing the impact gap. Experimental data are used to validate the mathematical model. The mathematical model allows a detailed nonlinear analysis, showing the rich response of the system, which includes dynamical jumps, bifurcations and chaos. In impact systems, discrepancies between numerical results and experimental measurements are common due to the difficulty in describing all factors that influence the resulting impact force profile. The use of wires to suspend the impacting body has the purpose to limit these uncertainties.